Digital Holography Technique for exposing Defect on Photovoltaic Cell - Abdullahi Bako; Bunyarit Voochaiyaphum; Prathan Buranasiri (My University, 2025)
We employed digital holography techniques to detect surface anomalies from photovoltaic cell. The approach allowed for precise spatial mapping of micro-crack features without requiring physical contact or electrical biasing compared to conventional methods.
Keywords: Digital Holography and Microscopy; Advanced Electron Microscopy Techniques and Applications; Integrated Circuits and Semiconductor Failure Analysis